1992
DOI: 10.1080/0962029920010208
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary View of Students’ Information Technology Experience across UK Initial Teacher Training Institutions

Abstract: Students enter initial teacher education institutions with a wide variety of experiences of information technology. This report aims to create a national perspective of their abilities and needs based on data collected independently by a number of institutions from England and Wales. For this preliminary survey data were provided by eight institutions. The survey covers 1370 students, of whom 731 were primary and 639 secondary. The data were gathered over a three year period (ending 1990/91) using a variety of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
3

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 6 publications
1
19
0
3
Order By: Relevance
“…Reports from Summers (1990) and McMahon & Gardner (1995) suggest that male students are less anxious about ICT and make more frequent use of it. Several other studies have reported that female students are less confident or knowledgeable than males about using computers (Blackmore et al, 1992;Oliver, 1993;Marshall, 1997;Marshall & Bannon, 1986). In contrast, there are also many reports which indicate that there are no significant differences between the attitudes of male and female students, for example: Koohang (1989), Kay (1989), Hunt & Bohlin (1993), Marshall & Bannon (1986) and Woodrow (1991).…”
Section: Literature Reviewmentioning
confidence: 80%
See 3 more Smart Citations
“…Reports from Summers (1990) and McMahon & Gardner (1995) suggest that male students are less anxious about ICT and make more frequent use of it. Several other studies have reported that female students are less confident or knowledgeable than males about using computers (Blackmore et al, 1992;Oliver, 1993;Marshall, 1997;Marshall & Bannon, 1986). In contrast, there are also many reports which indicate that there are no significant differences between the attitudes of male and female students, for example: Koohang (1989), Kay (1989), Hunt & Bohlin (1993), Marshall & Bannon (1986) and Woodrow (1991).…”
Section: Literature Reviewmentioning
confidence: 80%
“…Conflicting reports have argued whether age is a significant factor in determining the extent of low student teacher ICT uptake (Woodrow, 1991;Blackmore et al, 1992;Liénard, 1995).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Blackmore et al, 1992;Mellar & Jackson 1992, 1994. However, these surveys concentrate mainly on whole cohorts and provide few insights into individual subject areas.…”
Section: Surveys Of Student Teachersmentioning
confidence: 99%